Analisis Tingkat Kesejahteraan Rumah Tangga Petani Pedesaan Di Desa Wehali Dan Desa Kletek Kecamatan Malaka Tengah Kabupaten Malaka - Yohanes Wilfrid Leki; Wiendiyati Wiendiyati; Marthen R. Pellokila (Buletin Ilmiah Impas, 2019)
ABSTRACT This study aims to identify income patterns, spending patterns and the level of welfare of rural farmer households. Research has been conducted in Malaka Regency in June-July 2018. The number of sample farmer households is determined based on the Slovin method of 84 respondents spread in two sample villages namely Wehali and Kletek Villages in Central Malaka Sub-District. Data analysis used quantitative analysis and the exchange rate of rural farmer households (NTPRP). The results of the study showed that from the aspect of farm household in come in Malaka District, Rp. 1,933,625 / month was considered still low and included in the category of not yet prosperous. The structure of household income is still dominated by agricultural income, where the majority of farmer households to obtain income are still oriented towards land yields as a source of livelihood. Judging by the total expenditure of farmer households in the amount of Rp. 1,520,291 / month allocated for expenditure on food as much as Rp. 829,045 / month or around 54.53% of the total expenditure of rural farmer households and amounting to Rp. 691,246 / month or around 45.46% of total expenditure allocated for non-food consumption. Whereas the Exchange Rate of Rural Farmer Households in Malaka Regency shows that farmer households are not included in the category of prosperity because NTPRP values of total expenditure